2019
DOI: 10.14309/ctg.0000000000000102
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Association Between Frailty and Sarcopenia in Patients With Cirrhosis

Abstract: OBJECTIVES: Frailty is prevalent in patients with cirrhosis and is hypothesized to result in part from sarcopenia, but the precise contribution of sarcopenia to frailty in this population is poorly understood. METHODS: Included were patients with cirrhosis from 2011 to 2014 who had an ambulatory frailty assessment and abdominal computed tomography scan within 3 months. Logistic regression assessed the associations between frailty (=Liver Frailty Index ≥… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 18 publications
2
17
2
1
Order By: Relevance
“…Sarcopenia in CLDs is indeed similar to physical frailty (41). Sarcopenia may be the dominant driver of the physical frailty phenotype, especially in LC patients where hepatic synthetic impairment may accelerate the skeletal muscle mass decrease (14,42,43). In our data, 13.5% of our patients had frailty, while Fozouni et al have reported that out of 291 LC patients, 54 LC patients (19%) had frailty (42).…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Sarcopenia in CLDs is indeed similar to physical frailty (41). Sarcopenia may be the dominant driver of the physical frailty phenotype, especially in LC patients where hepatic synthetic impairment may accelerate the skeletal muscle mass decrease (14,42,43). In our data, 13.5% of our patients had frailty, while Fozouni et al have reported that out of 291 LC patients, 54 LC patients (19%) had frailty (42).…”
Section: Discussionsupporting
confidence: 63%
“…In our data, 13.5% of our patients had frailty, while Fozouni et al have reported that out of 291 LC patients, 54 LC patients (19%) had frailty (42). This is probably due to the difference of background patient population (prevalence of LC: 35.8% in our data vs. 100% in the study by Fozouni et al) (42). Age-stratified meta-analyses reported by Kojima et al have demonstrated that the pooled prevalence of frailty among elderly people living in Japan was 1.9% (65-69 years), 3.8% (70-74 years), 10.0% (75-79 years), 20.4% (80-84 years), and 35.1% (85 years or more) (44).…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…144 Sarcopenia can also manifest as frailty, which is an independent predictor of mortality in patients with cirrhosis. 145,146 The relationship between frailty and sarcopenia is stronger in men than in women. 145 The direct impact of frailty on the risk of HE is unknown.…”
Section: Malnutritionmentioning
confidence: 99%
“…Given that the liver plays a vital role in protein, glucose, lipid, and energy metabolism, LC is frequently complicated by protein–energy malnutrition (PEM), which can lead to sarcopenia [ 1 ]. In real-world clinical settings, the prevalence of sarcopenia in patients with LC ranges from 16.7% to 36.1% [ 4 , 5 , 6 , 7 ]. Accordingly, early comprehensive assessment and treatment intervention for sarcopenia are indispensable in patients with LC.…”
Section: Introductionmentioning
confidence: 99%